Analyzing, Designing, Developing and Enriching the Arabic Language Environment (ALE) among the undergraduate AFL Learners - Zubair, K. M. A. Ahamed (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
This research gives an overview of the initiatives undertaken at the New College, located in Chennai, Tamil Nadu, Southern India, aimed at enriching the Arabic language environment among undergraduate AFL learners, its planning, cultivating love for the Arabic Language while fostering a passion for the Arabic Language through an Arabic Environment. Utilizing qualitative and descriptive research methods, data were gathered through observation, interviews, and documentation. Findings reveal four types of programs, weekly, monthly, and supported by thorough planning, designing, and enrichment of research components. Challenges arise from the absence of a written guideline for forming, designing, and enriching programs, leading to the use of observe, imitate, and modify approaches for improvement in further implementations